(untitled) (Journal of Accessibility and Design for All, 2021)
Although there is literature published by a considerable number of scientific publications regarding disability and transport, the affected persons are only very rarely involved in the research. The paper presents the results of two qualitative studies conducted jointly with persons with different forms of disabilities: i) a social media content analysis and ii) peer-to-peer interviews with persons with disabilities (N = 49). The studies aimed to identify barriers that persons with access needs face during their trips with public transport. In line with a participatory approach, persons with disabilities from seven European cities were involved in conducting the research allowing for new interpretations of transport equity issues. Qualitative content analysis of both studies revealed barriers clustered into eight categories: regulations, public awareness and assistance, information provision and communication, infrastructure, vehicles, general service quality, stops and stations and emotional barriers. The two studies highlight important factors that influence disabled users’ experiences of public transport. Upon reflection, the paper derives research hypotheses and demonstrates the value of involving people with disabilities in the analysis of disability research to derive in-depth insights about equity in transport.